The impact of CP12 on the metabolome of cyanobacteria under fluctuating CO2 conditions - Lucius, Stefan; Arrivault, Stéphanie; Feil, Regina; Alvarenga-Lucius, Luna; Hagemann, Martin (Frontiers in Plant Science, 2025)
All organisms that perform oxygenic photosynthesis fix inorganic CO2 through the Calvin-Benson-Bassham (CBB) cycle, which is then converted into many organic compounds in associated pathways of primary carbon and nitrogen metabolism. Autotrophic CO2 fixation is only possible in the light, while under dark conditions, phototrophs adopt a heterotrophic lifestyle using stored organic carbon reserves. The switch between autotrophic and heterotrophic lifestyles often involves the activation and inactivation of key enzymes by redox regulation, including the regulatory protein CP12. In the present study, we analyzed the primary metabolism of the model cyanobacterium Synechocystis sp. PCC 6803 under different CO2 conditions in continuous light using targeted metabolomics. The comparison of wild type and a mutant with deleted CP12 showed that this regulatory protein is crucial for the acclimation of the metabolism when shifted for 1 h or 3 h from high to low CO2. Especially 1 h after shift from high into low CO2, many metabolites of the primary carbon and nitrogen metabolism showed a strong transient increase in the mutant Δcp12. Moreover, distinct differences were also observed when the strains were grown for longer times at high or low CO2 conditions. Collectively, our results show that the absence of CP12 not only affected the CBB cycle under diurnal conditions but also had a marked impact on glycogen catabolism and associated nitrogen metabolism in cyanobacteria exposed to different CO2 conditions in continuous light.